Preface - French, Christine (Victoria University of Wellington Law Review, 2016)
This article serves as the preface to a special issue of the Victoria University of Wellington Law Review including the papers presented at the inaugural New Zealand Private Law Scholars' Roundtable in February 2016. The author, Justice Christine French of the Court of Appeal of New Zealand, praises the papers for their quality of work, the broad range of topics, and the collaborative nature of the work and its New Zealand setting.